تدبير ومعالجة الحنف الولادي - يوسف صفوان; جوني أحمد; حسن أحمد (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 40 حالة قدم حنفاء عند 24 مريضاً، 16ذكر (%66,7)، 8 إناث (%33,3). معدل إصابة الإناث إلى الذكور1: 2. تراوحت أعمار المرضى من الولادة حتى ست سنوات. كان العلاج المحافظ ناجحاً في 20قدم من أصل 40 بنسبة (%50). في حين خضعت 17حالة لعلاج جراحي، والذي كان ناجحاً في 11حالة منها (%64,6). الاختلاط الأكثر ظهوراً بعد المعالجة هو تقريب مقدمة القدم(%15). النكس بعد العلاج الجراحي (%11,5). The study included 40 cases of clubfoot in 24patients: 16 females (66.7%) and 8 males (33.3%). The female to male ratio was 2:1, the patients’ age ranged from birthday to 6 years. The conservative treatment was successful in 20 foot from 40 (50%), while 17 cases underwent surgical treatment, which was successful in 11 cases (64,6%). The complication most visible after treatment was forefoot adductor (15%). Recurrence after surgical was treatment 11.5%.